Influence of nitrogen foliar application on growth, physiology and productivity of sunflower (Helianthus annuus L.) - Basir Ahmad Sarvari; Vinod Kumar Singh; Kapila Shekhawat; H. Obaid; Buahanuddin Wiqar (Annals of Agricultural Research, 2022)
A field experiment was conducted at the research farm of National Agricultural Science and Technology University (ANASTU), Kandahar, Afghanistan during summer season of 2017 in the sandy clay loam soil to evaluate the effect of foliar application of nitrogen on growth, physiology and productivity of sunflower. The twelve treatments of the experiment were laid out a randomized block design with three replications. Based on the results, it is concluded that the application of 50 kg N/ha as basal + 1.5% urea foliar spray at 20 and 40 DAS recorded significantly maximum plant height and leaf area at different plant growth stages. The maximum days to 50% flowering (58 days), root length (25.7 cm) and highest seed yield (2461 kg/ha) was also recorded under the same treatment. However, this treatment was found significantly at par where 50 kg N/ha was applied at the time of sowing, followed by one 1.5% foliar spray either at 20 or 40 DAS. Thus, a foliar spray of 1.5% N, either at 20 or 40 DAS along with 50 kg N/ha as basal resulted in higher growth, physiological parameters and productivity in sunflower under the semi-arid conditions of Afghanistan.